Študije primerov EPF: Razvoj, trajnost in inovacije v poslovni praksi 2024 - Ošlovnik, Tinkara; Iztok, Kolar; Širec, Karin; Teskač, Nina; Tešić, Neca; Zdolšek, Daniel; Belak, Jernej; Elias, Arun A.; Bradač Hojnik, Barbara; Korez Vide, Romana; Hunjet, Anica; Sesar, Vesna; et al. (2024)
FEB Case Studies: Development, Sustainability, and Innovation in Business Practice 2024. The monograph FEB Case Studies: Development, Sustainability, and Innovation in Business Practice 2024 presents a collection of case studies that illustrate contemporary challenges in the economy while providing insights into innovative and sustainable business practices. It focuses on business development, sustainable operations, and innovation, addressing topics such as eco-design, sustainable business models, strategic growth management, financial decision-making, controlling, digital transformation, and global value chains, bridging academic knowledge with real-world business challenges. Through practical examples, the authors demonstrate how companies develop competitive advantages, make key decisions, and adapt to changes in a sustainable and innovative manner. Primarily intended for students of economics and business, the publication enables a deeper understanding of theoretical concepts through real-world cases while also serving as a valuable resource for educators, researchers, and professionals. By combining theoretical foundations with practical case studies, it provides an essential source of knowledge for anyone engaged in contemporary economic and business challenges.
Keywords: Faculty of Economics and Business; case studies; economics and business sciences; innovation; sustainable business; strategic management; business development